Cover Picture: Control of Perovskite Crystal Growth by Methylammonium Lead Chloride Templating (Chem. Asian J. 8/2016). Issue 8 (29th March 2016) - Binek, Andreas; Grill, Irene; Huber, Niklas; Peters, Kristina; Hufnagel, Alexander G.; Handloser, Matthias; Docampo, Pablo; Hartschuh, Achim; Bein, Thomas
Abstract : The combination of a chloride‐based precursor and the slow evaporation of the solvent in the formation of MAPbI3 generate uniform, orientated and big crystals (see Cover image, right side) in comparison to commonly used synthesis procedures (left side). A crystallization mechanism is proposed where MAPbCl3 acts as template for MAPbI3 and, by extending the time for template formation, it is shown that the charge‐carrier mobility doubles. The results give a deeper understanding of the influence of chloride in the synthesis of MAPbI3 and illustrate the importance of carefully controlling crystallization for reproducible, high‐efficiency solar cells. More information can be found in the Communication by Thomas Bein et al. onpage 1199 in Issue 8, 2016 (DOI:10.1002/asia.201501379 ). Image by Christoph Hohmann, Nanosystems Initiative Munich (NIM).